Applied Cerebral Angiography : Normal Anatomy and Vascular Pathology - Bradac, Gianni Boris (Springer International Publishing : Imprint: Springer, 2017)
This book offers detailed guidance on the diagnostic use of cerebral angiography based on precise description of the angiographic appearances of normal anatomy and pathological conditions. In this third edition, every chapter has been thoroughly revised and enlarged to reflect new knowledge and experiences, and more attention is paid to the correlations between anatomopathological findings and clinical manifestations. Beyond explaining the diagnostic value of cerebral angiography, a key aim is to equip readers with the precise knowledge of the anatomy of cerebral vessels required for optimal application of endovascular therapy of pathologies involving the arteries and veins of the brain. As in preceding editions, the book is divided into two parts. The first part describes the normal anatomy, with attention to morphological aspects, embryological development, function, and vascular territories. The intraorbital and extracranial vascularization is also fully considered. The knowledge provided will serve as a sound basis for the correct interpretation of pathological processes and their clinical significance, as covered in depth in the second part of the book. .
Keywords: Medicine.; Neuroradiology.; Angiology.; Neurology.; elektronické knihy; electronic books